Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

Use the substitution method to solve y= -7x + 3=

Sagot :

y= -7x + 3
y + 7x = -7x + 7x + 3
y = 7x + 3
7x + 3 = -7x + 3
+7x        +7x     
14x + 3 = 3
         -3  -3
     14x = 0
      14    14
         x = 0
y = -7(0) + 3
y = 0 + 3
y = 3
(x, y) = (0, 3)
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.